Telegram
026-0017-001 Charges to pay RECEIVED Telegraph Office, E.C.I. POST OFFICE TELEGRAM Prefix. Time handed in. Office of Origin and Service Instructions. Words. 17 No. OFFICE STAMP 0583 LONDON S.W.D.O 18AUG39 317 3.2 MANCHESTER 10 BELL TRADUNIC SOWEST LONDON = ROUEN STEAMER PROGRESS 24 TH = WHOLESALE EXPORT + + + CT 24 TH + + + For free repetition of doubtful word [text obscured] call, with this form at office of delivery. Other enquiries should be accompanied by this form and, if possible, the envelope. 292/946/26/17